Experiência do cooperativismo e o empoderamento dos associados da Cooperativa Ambiente – Vila Estrutural (Brasília, Distrito Federal) - Rodrigues, Viviane da Silva Bernardes (Universidade do Vale do Rio dos Sinos, 2018)
The emergence of associations and cooperatives of recyclable waste collectors constitute an important initiative, since they involve both financial improvements and minimizing the vulnerability of waste pickers. This research aimed to analyze the experience of cooperativism and the empowerment of the cooperative. The research was conducted together with the Environment cooperative located in the region of Estrutural, Brasília-DF. The correlation between the experience of cooperativism and the empowerment of the cooperative was analyzed from a theoretical and methodological perspective. For this purpose, the exploratory and descriptive research strategy was used by, using interview and participant observation as techniques for collecting data. The results indicated the existence of empowerment processes in the different levels studied but with limits. Such workers have sought social recognition, through attempts to make visible the activities of sorting and recycling of waste and to establish themselves as a specific occupational category, through their political organization, which contributes to their empowerment, individually and collectively. However, there are limits to individual empowerment, since the collectors benefit from the guarantees of a cooperative, but with restrictions, due to non-compliance with certain cooperative principles.
Keywords: Cooperativas; Princípios cooperativistas; Empoderamento; Cooperatives; Cooperative principles; Empowerment; ACCNPQ::Ciências Humanas::Sociologia